A Young Male with Abdominal Distension and Per Rectal Bleeding - Afroj, Roksana; Hossain, AZM Mostaque; Khan, Mohammad Ashraf Uddin; Alam, SM Syeed Ul (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Abstract not available J Bangladesh Coll Phys Surg 2014; 32: 178